Running With Scissors: Evolutionary Conflicts Between Viral Proteases and the Host Immune System - Tsu, Brian V.; Fay, Elizabeth J.; Nguyen, Katelyn T.; Corley, Miles R.; Hosuru, Bindhu; Dominguez, Viviana A.; Daugherty, Matthew D. (Frontiers in Immunology, 2021)
Many pathogens encode proteases that serve to antagonize the host immune system. In particular, viruses with a positive-sense single-stranded RNA genome ((+)ssRNA), including picornaviruses, flaviviruses, and coronaviruses, encode proteases that are not only required for processing viral polyproteins into functional units but also manipulate crucial host cellular processes through their proteolytic activity. Because these proteases must cleave numerous polyprotein sites as well as diverse host targets, evolution of these viral proteases is expected to be highly constrained. However, despite this strong evolutionary constraint, mounting evidence suggests that viral proteases such as picornavirus 3C, flavivirus NS3, and coronavirus 3CL, are engaged in molecular ‘arms races’ with their targeted host factors, resulting in host- and virus-specific determinants of protease cleavage. In cases where protease-mediated cleavage results in host immune inactivation, recurrent host gene evolution can result in avoidance of cleavage by viral proteases. In other cases, such as recently described examples in NLRP1 and CARD8, hosts have evolved ‘tripwire’ sequences that mimic protease cleavage sites and activate an immune response upon cleavage. In both cases, host evolution may be responsible for driving viral protease evolution, helping explain why viral proteases and polyprotein sites are divergent among related viruses despite such strong evolutionary constraint. Importantly, these evolutionary conflicts result in diverse protease-host interactions even within closely related host and viral species, thereby contributing to host range, zoonotic potential, and pathogenicity of viral infection. Such examples highlight the importance of examining viral protease-host interactions through an evolutionary lens.